2018
DOI: 10.1371/journal.pone.0194726
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and distribution of Senegalia senegal (L.) Britton under climate change scenarios in West Africa

Abstract: Climate change is predicted to impact species’ genetic diversity and distribution. We used Senegalia senegal (L.) Britton, an economically important species distributed in the Sudano-Sahelian savannah belt of West Africa, to investigate the impact of climate change on intraspecific genetic diversity and distribution. We used ten nuclear and two plastid microsatellite markers to assess genetic variation, population structure and differentiation across thirteen sites in West Africa. We projected suitable range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 75 publications
1
10
1
Order By: Relevance
“…The absence of clear‐cut genetic discontinuities over large distances for A. africana and A. quanzensis is consistent with results reported in the savannah tree species Adansonia digitata and Khaya senegalensis , which showed no geographic discontinuities of the genetic variation (Tsy et al., ; Sexton et al., ). Acacia senegal displays strong differentiation between Sudanian and Zambezian populations, but low diversity and structure at a nuclear ribosomal marker across the Sudanian savannahs suggest a recent range expansion (Odee et al., , but see Lyam et al., ). These results suggest that the African savannahs have not experienced major upheavals that led to their fragmentation (Salzmann et al., ; Vincens et al., ; Watrin et al., ), in contrast to the major fluctuations of the rainforest cover over time (Maley, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of clear‐cut genetic discontinuities over large distances for A. africana and A. quanzensis is consistent with results reported in the savannah tree species Adansonia digitata and Khaya senegalensis , which showed no geographic discontinuities of the genetic variation (Tsy et al., ; Sexton et al., ). Acacia senegal displays strong differentiation between Sudanian and Zambezian populations, but low diversity and structure at a nuclear ribosomal marker across the Sudanian savannahs suggest a recent range expansion (Odee et al., , but see Lyam et al., ). These results suggest that the African savannahs have not experienced major upheavals that led to their fragmentation (Salzmann et al., ; Vincens et al., ; Watrin et al., ), in contrast to the major fluctuations of the rainforest cover over time (Maley, ).…”
Section: Discussionmentioning
confidence: 99%
“…Three of the species occur in the Sudanian savannah (northern hemisphere): the shea tree (Vitellaria paradoxa; Allal et al, 2011;Logossa et al, 2011), the African mahogany (Khaya senegalensis; Sexton et al, 2015), and the locust bean (Parkia biglobosa; Lompo et al, 2018). The other two species have a Sudano-Zambezian distribution (northern and southern hemispheres): the baobab (Adansonia digitata; Tsy et al, 2009;Kyndt et al, 2009) and Arabic gum (Acacia senegal; Odee et al, 2012;Lyam et al, 2018). Within the Sudanian savannah, weak genetic structure was detected in K. senegalensis and A. digitata, while moderate differentiation was found in A. senegal, mostly in chloroplast markers.…”
mentioning
confidence: 99%
“…Historical distribution and range dynamics of S. senegal indicate variation along climatic and edaphic regimes, separating the eastern and southern ranges from the western and central African ranges 27 . In addition, population genetic studies of Kenyan and West African populations of S. senegal have shown that anthropogenic perturbations and climatic shifts could impact levels of genetic diversity (GD), population sizes, structure of gene pools, and natural regeneration patterns of the species at regional scale 6 , 39 . Investigating the impact of climate change on GD of S. senegal will provide insights into population structure, and can further advance our understanding of the genetic consequences of post-glacial expansion processes and climate warming on the future distribution of genetic variation.…”
Section: Introductionmentioning
confidence: 99%
“…Senegalia Senegal can attain a height of 5-12 m, and grows on sandy, skeletal and slightly loamy soils, with a soil pH of 5-8. The gum acacia also grows in areas that receive 100-950 mm annual rainfall (Lyam et al, 2018). It can tolerate five to 11 months of drought and can survive temperatures high as 43 °C, dry wind, and sandstorms.…”
Section: Introductionmentioning
confidence: 99%